Sinus lift procedures in dental implants: A literature review on techniques, recommendations, and complications - S Devameena; D S Dinesh; G LakshmiDevi; G Shanmugavadivel (Wolters Kluwer Medknow Publications, 2020)
Posterior atrophic maxilla with pneumatized sinus often challenges dental implant surgery. Sinus lift in order to augment the residual alveolar ridge height resulted in various sinus lift surgical techniques. Sinus augmentation in atrophic maxilla transforms the atrophic posterior maxilla to a favorable place for implant placement. Additional surgery of sinus lift during implant placement becomes a difficult decision for both dentist and patient. This literature search focuses on many valuable articles that support evidence on the treatment options and predictable increase in bone height after sinus lift procedure. This literature review explains on the classification of posterior atropic maxilla and its treatment options, sinus lift techniques, recommendations, complications, and a precise discussion that supports this procedure.